2003
DOI: 10.1590/s0104-66322003000200005
|View full text |Cite
|
Sign up to set email alerts
|

Indium recovery from acidic aqueous solutions by solvent extraction with D2EHPA: a statistical approach to the experimental design

Abstract: This experimental work presents the optimization results of obtaining a high indium concentration solution and minimum iron poisoning by solvent extraction with D2EHPA solubilized in isoparaffin and exxsol. The variables studied in the extraction step were D2EHPA concentration, acidity of the aqueous phase and time of contact between phases. Different hydrochloric and sulfuric acid concentrations were studied for the stripping step. The optimum experimental conditions resulted in a solution with 99% indium ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Thus, many studies have been carried out to recover valuable material from scrap LCD screens. Most studies have concentrated on hydrometallurgical methods (Hsieh et al, 2009) such as acid dissolution or acid leaching (Li et al, 2009;Li et al, 2011;Gabriel et al, 2017a;Gabriel et al, 2017b), solvent extraction (Fortes et al, 2003;Honma and Muratani, 2005) and chlorination (Park et al, 2009) methods. However, those studies require the need for wastewater treatment after recovering the metals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many studies have been carried out to recover valuable material from scrap LCD screens. Most studies have concentrated on hydrometallurgical methods (Hsieh et al, 2009) such as acid dissolution or acid leaching (Li et al, 2009;Li et al, 2011;Gabriel et al, 2017a;Gabriel et al, 2017b), solvent extraction (Fortes et al, 2003;Honma and Muratani, 2005) and chlorination (Park et al, 2009) methods. However, those studies require the need for wastewater treatment after recovering the metals.…”
Section: Introductionmentioning
confidence: 99%
“…Fortes et al . indicated that lower diluent volume in the organic phase resulted in less oxidation of ferrous ions.…”
Section: Introductionmentioning
confidence: 99%
“…Rezaei and Nedjate [33] reported that when diluents with lower dielectric constants were used, a more selective extraction of the metal from acidic solution could be achieved. Fortes et al [27] indicated that lower diluent volume in the organic phase resulted in less oxidation of ferrous ions.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent extraction [7,8], hydrometallurgical [9] and chlorination [10,11] methods have also been reported to recover ITO from etching solutions or target. However, due to complications in the above processes, a simpler treatment method by means of sub-critical water (hereafter called sub-CW) technology was initiated by our group [12].…”
Section: Introductionmentioning
confidence: 99%